The mitochondrial epigenome: a role in Alzheimer's disease?. (December 2014) - Devall, Matthew; Mill, Jonathan; Lunnon, Katie
Considerable evidence suggests that mitochondrial dysfunction occurs early in Alzheimer's disease, both in affected brain regions and in leukocytes, potentially precipitating neurodegeneration through increased oxidative stress. Epigenetic processes are emerging as a dynamic mechanism through which environmental signals may contribute to cellular changes, leading to neuropathology and disease. Until recently, little attention was given to the mitochondrial epigenome itself, as preliminary studies indicated an absence of DNA modifications. However, recent research has demonstrated that epigenetic changes to the mitochondrial genome do occur, potentially playing an important role in several disorders characterized by mitochondrial dysfunction. This review explores the potential role of mitochondrial epigenetic dysfunction in Alzheimer's disease etiology and discusses some technical issues pertinent to the study of these processes.